2022
DOI: 10.1111/jth.15615
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of bleeding and thromboembolism and impact on overall survival in adult patients with hemophagocytic lymphohistiocytosis: A 20‐year provincial retrospective cohort study

Abstract: Background Hemophagocytic lymphohistiocytosis (HLH) is a rare syndrome characterized by uncontrolled immune activation and high risk of death. There is scarce data on the incidence of bleeding and thromboembolism in HLH. Objectives To determine the cumulative incidence of bleeding and thromboembolism and impact on survival in adults with HLH. Patients/Methods We conducted a multicenter retrospective cohort study of adults with HLH in Alberta, Canada (1999–2019). The cumulative incidence of bleeding and thrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…70 Another recent review reported VTE in 11% and bleeding in 40%. 71 This contrasts with the CAR-T studies, where bleeding has been reported less frequently. 11 CAR-T patients may also develop toxicities resembling HLH, sometimes referred to as carHLH in the literature.…”
Section: Do Ca R-ts Cause H a E Moph Ag Oc Y Tic Ly M Phohistioc Y To...mentioning
confidence: 89%
See 1 more Smart Citation
“…70 Another recent review reported VTE in 11% and bleeding in 40%. 71 This contrasts with the CAR-T studies, where bleeding has been reported less frequently. 11 CAR-T patients may also develop toxicities resembling HLH, sometimes referred to as carHLH in the literature.…”
Section: Do Ca R-ts Cause H a E Moph Ag Oc Y Tic Ly M Phohistioc Y To...mentioning
confidence: 89%
“…Hypofibrinogenaemia was significantly associated with bleeding, which occurred in 22% (4.3% fatal) 70 . Another recent review reported VTE in 11% and bleeding in 40% 71 . This contrasts with the CAR‐T studies, where bleeding has been reported less frequently 11 …”
Section: Do Car‐ts Cause Haemophagocytic Lymphohistiocytosis?mentioning
confidence: 95%
“… 18 Endothelial or vascular injury and a procoagulant state leading to acute features of TMA are also likely mediated by abnormal activation of the immune system in HLH: TMA has been variably reported (13%–70%) to occur in HLH. 19 , 20 Gloude et al. 19 describe resolution of TMA and survival after treatment that included eculizumab and emapalumab (an interferon gamma blocker) in a small group of patients developing TMA in HLH.…”
Section: Discussionmentioning
confidence: 99%
“…e selection of effective firstline induction therapy can to a large extent improve the serious and bad basic condition of patients in the early stage of treatment and create conditions for survival and further clear diagnosis of potential diseases and targeted treatment. Bleeding in deep organs is the main risk of acute death before treatment takes effect [17,18]. As a coagulation factor, serum calcium is a risk factor for bleeding events in patients.…”
Section: Discussionmentioning
confidence: 99%